Predlogi za izboljšanje sistema funkcij gozdov v Sloveniji - Planinšek, Špela (Gozdarski vestnik, 2012)
This research explores the history and development of forests functions in Slovenia in comparison to four selected European countries and three international forest processes. It describes the attitude of people towards them and the potential for planning and monitoring of functions in space and time. Literature review helps to evaluate the importance of forest functions in the selected European countries and the parallels or the shortcomings between international trends in relation to forest functions, services and goods. A quantity of new services is showing up when looking across Slovenian borders; people increasingly recognize them and require from intensive forest planning. Given the trends we should maintain the main groups of the functions(ecological, social, production) and exclude at least recreational services and biodiversity function as separate groups. The results will help to prepare guidelines for the improvement of system of forest functions, services, and goods planning processes beginning with the determination of functional units. The objective is to improve the system of forest functions, making it more unique and useful for monitoring the current state and progress of functional units.
Keywords: funkcije gozdov; storitve gozdov; dobrine gozdov; kartiranje; konflikti; načrtovanje; mednarodne smernice